Kontribusi Industri Film Korea Selatan Dalam Membangun Citra Nasional: Pelajaran Apa Yang Dapat Diambil Oleh Indonesia? - Salsabila Khairunnisa; Agus Trihartono; Fuat Albayumi (Majalah Ilmiah DIAN ILMU, 2022)
This article explains the efforts made by South Korea in building a national image through the film industry. Furthermore, this article explains the lessons that Indonesia can take from South Korea in strengthening nation branding through the development of the Indonesian film industry. This study uses a qualitative descriptive method with secondary data sources obtained through literature studies. This research shows the efforts of government actors by providing financial assistance, promotion, and providing supporting facilities for filmmaking. Meanwhile, the role of South Korean non-government actors is to assist in the entire pre-production process to the promotion of South Korean films. South Korea's success in building a national image through the film industry can be a good example for the Indonesian film industry. Indonesia can strengthen the role of government and non-government to develop the film industry like South Korea. In addition, Indonesia can provide support to its film industry, starting from pre-production activities to promotions.